Influence of the single or combined administration of cocaine and testosterone in autonomic and neuroendocrine responses to acute restraint stress - Cruz, Fabio C. [UNESP]; Engi, Sheila A. [UNESP]; Leao, Rodrigo M. [UNESP]; Planeta, Cleopatra da Silva [UNESP]; Crestani, Carlos Cesar [UNESP] (Sage Publications Ltd, 2012)
Abuse of cocaine and androgenic-anabolic steroids (AASs) has become a serious public health problem. Despite reports of an increase in the incidence of simultaneous abuse of these substances, potential toxic interactions between cocaine and AASs are poorly known. In the present study, we investigated the effects of either single or combined administration of testosterone and cocaine for one or 10 consecutive days on autonomic (arterial pressure, heart rate and tail cutaneous temperature) and neuroendocrine (plasma corticosterone) responses induced by acute restraint stress in rats. Combined administration of testosterone and cocaine for 10 days reduced the increase in heart rate and plasma corticosterone level, as well as the fall in tail skin temperature induced by restraint stress. Furthermore, repeated administration of cocaine inhibited the increase in arterial pressure observed during restraint, and this effect was not affected by coadministration of testosterone. Ten-day combined administration of testosterone and cocaine increased basal values of arterial pressure. Moreover, chronic administration of testosterone induced rest bradycardia and elevated basal level of plasma corticosterone. One-day single or combined administration of the drugs did not affect any parameter investigated. In conclusion, the present study demonstrated that combined administration of testosterone and cocaine changed the autonomic and neuroendocrine responses to acute restraint stress. These findings suggest that interaction between AASs and cocaine may affect the ability to cope with stressful events.
Keywords: Abuse; anabolic steroids; androgens; cocaine; interaction; stress; cardiovascular; HPA axis; glucocorticoids